Reforming Islamic Family Law in Iraq: A Study of Marriage, Child Marriage, and Inheritance - Maulana, Ramza Fatria; Fauzi Dahrial (Institute of Educational, Research, and Community Service)
Islamic family law represents one of the most dynamic areas of legal transformation within Muslim-majority countries, including Iraq, a nation characterized by deep social, historical, and sectarian complexity. This study aims to analyze the dynamics of Islamic family law in Iraq, focusing on marriage, child marriage, and inheritance within the framework of Personal Status Law No. 188 of 1959. A qualitative method was employed using a normative-juridical and historical-sociological approach, based on literature reviews of statutory laws, fiqh texts, academic journals, and international reports, analyzed through descriptive-qualitative techniques. The findings indicate that Iraq adopts an eclectic legal approach, combining principles from both Sunni and Shia jurisprudence to establish a more inclusive family law system. However, legal loopholes in the regulation of minimum marriage age, gender-based discrimination in inheritance, and discrepancies between statutory norms and social practices remain significant challenges. In conclusion, the dynamics of Islamic family law in Iraq reflect an ongoing negotiation between classical fiqh traditions, national legal reforms, and evolving international human rights standards